2008
DOI: 10.1007/s00418-008-0432-9
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Connexin 43 in normal canine testes and canine testicular tumors

Abstract: In human testis, gap junctions containing connexin(Cx)43 are located within the seminiferous epithelium between Sertoli cells and between Sertoli and germ cells. Cx43 is known to play a role in the differentiation and proliferation of these cell types. It can further be associated with human seminoma development. The dog has been proposed as a model for studies of the male reproductive system, because of the frequent occurrence of testicular neoplasms. Thus, we investigated Cx43-mRNA and -protein expression in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 61 publications
1
12
0
Order By: Relevance
“…The onset of the meiosis was accompanied by a peak in tubular Cx43 protein levels as if the two events were related. Our observation is consistent with the localization of Cx43 mRNA to primary spermatocytes (72) and spermatogonia (6,9,72). Our observation of low Cx43 mRNA and protein levels during the two spermatogonial stem cell proliferation periods is in line with the concept that the cells' ability to communicate through gap junctions is inversely related to their growth activity (70,71), with the mitotic cells being weakly coupled among themselves, and with other in- terphasic cells in most systems (24,48).…”
Section: Cx43 Germ Cell Mitosis and The Acquisition Of Meiotic Compsupporting
confidence: 92%
“…The onset of the meiosis was accompanied by a peak in tubular Cx43 protein levels as if the two events were related. Our observation is consistent with the localization of Cx43 mRNA to primary spermatocytes (72) and spermatogonia (6,9,72). Our observation of low Cx43 mRNA and protein levels during the two spermatogonial stem cell proliferation periods is in line with the concept that the cells' ability to communicate through gap junctions is inversely related to their growth activity (70,71), with the mitotic cells being weakly coupled among themselves, and with other in- terphasic cells in most systems (24,48).…”
Section: Cx43 Germ Cell Mitosis and The Acquisition Of Meiotic Compsupporting
confidence: 92%
“…Fink et al (2009) reported that claudin-11 is overexpressed and mislocated from the blood-testis barrier in Sertoli cells of testicular intraepithelial neoplasia, which led the authors to speculate that a dysfunction of claudin-11 rather than a failure of expression leads to disruption of the blood-testis barrier in testicular intraepithelial neoplasia. Another study by Ruttinger et al (2008) investigated the expression of Cx43 in the context of testicular neoplasia of the dog. In canine testicular tumors Cx43 mRNA was detectable in both seminoma and neoplastic Sertoli cells, but Cx43 at the protein level was found only in neoplastic Sertoli cells.…”
Section: Male Reproductive Systemmentioning
confidence: 99%
“…Indeed, mRNAs for Cx26, Cx31, Cx32, Cx33, Cx37, Cx40, Cx43 and Cx45 were found in rodents [25,27,28], whereas only Cx26, Cx32, Cx33, Cx43 were detected at the protein level [18,26,27,29,30]. Cx43 was found in Sertoli cells of numerous species, like human, mouse, rat, pork, brook trout and dog [26,[31][32][33][34].…”
Section: Testismentioning
confidence: 99%
“…For other species, however, the knowledge on Cx expression in germ cell lineage is highly limited, since only few studies were performed. Cx43 was detected in human and dog germ cells [33,34,38].…”
Section: Testismentioning
confidence: 99%